Surface modification method for improving water flux and anti-pollution capability of nanofiltration ceramic membrane

By growing TiO2 nanoparticles on the surface of the ceramic support, a uniformly distributed TiO2 nanofiltration membrane is formed, which solves the problems of low water flux and insufficient anti-fouling ability of the nanofiltration ceramic membrane, and significantly improves the water flux and anti-fouling ability of the membrane.

CN119607912APending Publication Date: 2025-03-14BEIJING INSTITUTE OF TECHNOLOGY ZHENGZHOU RESEARCH INSTITUTE
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411793876.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The nanofiltration ceramic membrane has low water flux and insufficient anti-fouling ability, which limits its application in the field of water treatment.

Method used

By growing TiO2 nanoparticles on the surface of the ceramic support, a uniformly distributed TiO2 nanofiltration membrane is formed, which improves the water flux and anti-fouling ability of the membrane. Specific steps include preparing an alumina dispersion, spraying or dipping on the ceramic support, sintering to form an intermediate layer and a nanoseparation layer, and finally drying in an oven to obtain a nanofiltration ceramic membrane with a uniform surface distribution of TiO2.

Benefits of technology

The water flux of the nanofiltration ceramic membrane was significantly improved, the water flux of the tubular membrane increased from 24L/m2.h.bar to 51L/m2.h.bar, and the water flux of the flat membrane increased from 20L/m2.h.bar to 38L/m2.h.bar, and the membrane's anti-fouling ability was improved. The flux recovery rate of the modified tube nanofiltration membrane with TiO2 surface modification layer reached 90.5%, and the flux reduction rate was only 19.1%.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a surface modification method for improving water flux and anti-pollution capability of a nanofiltration ceramic membrane, which comprises the following steps: S1, heating and dissolving methyl cellulose in deionized water, and adding TiO2 sol and alumina powder to prepare an alumina dispersion liquid, S2, spraying the alumina dispersion liquid on a ceramic support body, drying and sintering to obtain the nanofiltration ceramic membrane. S3, heating and dissolving polyvinyl alcohol in deionized water to obtain a polyvinyl alcohol aqueous solution, and diluting boehmite sol with the polyvinyl alcohol aqueous solution, S4, spraying the boehmite sol on the middle layer, drying and sintering to obtain a ceramic support body A, and S5, melting tetraisopropyl titanate into an ethanol solution to form a mixed solution, immersing the ceramic support body A into the mixed solution, and drying to obtain a ceramic support body B; acetic acid is dissolved in ultrapure water and slowly dropwise added into the mixed solution, after dropwise adding is finished, a reaction is waited for a period of time, drying is conducted, and then the nanofiltration ceramic membrane can be obtained, and the method has the advantages that the water flux and the anti-pollution capacity of the nanofiltration ceramic membrane are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of membrane separation, and in particular relates to a surface modification method for improving the water flux and anti-fouling ability of a nanofiltration ceramic membrane. Background Art

[0002] Membrane separation technology has shown great advantages in water treatment due to its high separation efficiency and high water resource reuse rate. Nanofiltration technology is a new type of pressure-driven membrane separation technology that started relatively late. It has the characteristics of high permeability and low operating pressure. It can replace traditional reverse osmosis technology in many occasions. Common nanofiltration membranes are composite structures, that is, they are composed of a porous support layer and a dense separation layer made of different materials. The design, preparation and optimization of the separation layer have an important influence on the overall performance of the composite membrane. However, the water flux of the nanofiltration separation layer is low and the membrane fouling is serious, which is the bottleneck restricting the development of nanofiltration membrane separation technology. Therefore, the research and development of high-flux, anti-pollution modified nanofiltration membranes has important theoretical significance and application value in the field of water treatment.

[0003] Zhong Zhaoxiang et al. [A method for preparing high-flux separation ceramic membrane based on phase inversion method, CN202311800518.9] can adjust the pore size and porosity of the ceramic membrane by controlling the types and addition amounts of ceramic powder, polymer, non-solvent additive, surfactant and polar solvent, and prepare a ceramic membrane with high porosity and high flux. However, the pore size of the ceramic membrane depends on the particle size of the ceramic powder. Since small-particle ceramic powder is easy to agglomerate, this method is not suitable for nanofiltration ceramic membranes.

[0004] Li et al. [Novel designed TFC membrane based on host-guest interactionfor organic solvent nanofiltration(0SN)[J].Journal of Membrane Science, 2019, 588:117227.] obtained MoS2 nanosheets by liquid phase exfoliation, and used them as nanofillers in the interfacial polymerization process to prepare reverse osmosis membranes. The addition of MoS2 can slow down the diffusion of water phase to the interface, making the thickness of the membrane's selective layer smaller. The optimal water flux of the membrane is 6.2L / (m2·h·bar), and the retention rate of NaCl is 98.6%. The improvement of the hydrophilicity of the membrane surface also improves the anti-fouling performance of the membrane. However, if this method is used on a ceramic substrate, the MoS2 crystals grown in situ on the ceramic surface are uncontrolled and cannot be evenly distributed. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a surface modification method that can effectively improve the water flux and anti-fouling ability of nanofiltration ceramic membranes.

[0006] The technical solution of the present invention is as follows:

[0007] A surface modification method for improving water flux and anti-fouling ability of nanofiltration ceramic membranes comprises the following steps:

[0008] S1. Dissolve methyl cellulose in deionized water by heating to obtain a methyl cellulose aqueous solution, then add TiO2 sol to the methyl cellulose aqueous solution to obtain a TiO2 aqueous solution, and finally add weighed alumina powder, stir magnetically for 10 minutes and then ultrasonicate for half an hour to obtain a 200 nm alumina dispersion;

[0009] S2. Spray or dip a layer of 200nm aluminum oxide dispersion on the ceramic support, dry at 100℃, and sinter at 800℃ for 1-3h to form a 50nm intermediate layer on the surface of the ceramic support;

[0010] S3, weigh polyvinyl alcohol and heat it in deionized water to dissolve it to obtain a polyvinyl alcohol aqueous solution, and then dilute the commercial boehmite sol with the polyvinyl alcohol aqueous solution from 20% to 2% to 8%, so as to obtain the desired boehmite sol of appropriate concentration;

[0011] S4, evenly spray or dip-coat a layer of boehmite sol of appropriate concentration on the middle layer of the ceramic support in step S2, dry at 100°C, and sinter at 600°C for 24h to form a nano separation layer on the surface of the middle layer, thereby obtaining a ceramic support A;

[0012] S5. Dissolve tetraisopropyl titanate in ethanol solution to form a mixed solution, immerse the ceramic support A obtained in step S4 into the mixed solution, dissolve acetic acid in ultrapure water, place it in a burette, and slowly drip it into the mixed solution immersed with the ceramic support A. After the dripping is completed, wait for a period of time for the reaction, take out the ceramic support A, rinse off excess TiO2 particles with ultrapure water, and dry it in an oven to obtain a nanofiltration ceramic membrane with TiO2 evenly distributed on the surface.

[0013] Furthermore, the concentration of methylcellulose in the methylcellulose aqueous solution in step S1 is in the range of 1% to 8%.

[0014] Furthermore, the TiO2 content of the TiO2 aqueous solution in step S1 is in the range of 0.5%-3%.

[0015] Further, the aluminum oxide content of the 200 nm aluminum oxide dispersion in step S1 is in the range of 3% to 8%;

[0016] Furthermore, the polyvinyl alcohol concentration of the polyvinyl alcohol aqueous solution in step S2 is 2%-5%.

[0017] Furthermore, in step S5, the volume range of acetic acid is 19 ml-60 ml, and the volume range of ultrapure water is 120 ml-360 ml.

[0018] Furthermore, in step S5, the waiting time for the reaction after the dropwise addition is completed is 30-40 minutes.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. The present invention grows TiO2 nanoparticles on the surface of a ceramic support to obtain a ceramic nanofiltration membrane, so that the water flux of the tubular membrane is increased from the original 24 (L / m2.h.bar) to 51 (L / m2.h.bar), and the water flux of the flat membrane is increased from the original 20 (L / m2.h.bar) to 38 (L / m2.h.bar). The anti-pollution ability of the tubular nanofiltration membrane before modification is compared (the flux recovery rate of the nanofiltration membrane is 85.9%, and the flux reduction rate is 32.4%). The flux recovery rate of the tubular nanofiltration membrane modified by the TiO2 surface modification layer reaches 90.5%, and the flux reduction rate is only 19.1%; the anti-pollution ability of the flat nanofiltration membrane before modification is compared (the flux recovery rate of the nanofiltration membrane is 81.3%, and the flux reduction rate is 39.6%). The flux recovery rate of the flat nanofiltration membrane modified by the TiO2 surface modification layer reaches 87.5%, and the flux reduction rate is only 22.4%. DETAILED DESCRIPTION

[0021] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] Example 1

[0023] A surface modification method for improving water flux and anti-fouling ability of nanofiltration ceramic membranes, comprising:

[0024] Experimental Materials

[0025] Alumina porous support (tubular membrane / flat membrane, pore size of 200nm, porosity of 41.3%); alumina (200nm, α-Al2O3, 99.9%); methyl cellulose (C20H38011); anhydrous ethanol (C2H60, ≥99.5%); TiO2 sol; boehmite sol (20%); polyvinyl alcohol (PVA, viscosity 30-50mpas); anhydrous acetic acid (CH3COOH, ≥99.5%); tetraisopropyl titanate (C12H2804Ti, analytical grade);

[0026] Implementation steps:

[0027] S1. Dissolve 10 g of methyl cellulose in 400 ml of deionized water at 85°C to obtain a methyl cellulose aqueous solution, then add 60 ml of 15% TiO2 sol to the methyl cellulose aqueous solution to obtain a TiO2 aqueous solution, and finally add 40 g of alumina powder, stir magnetically for 10 min, and then ultrasonicate for half an hour to obtain a 200 nm alumina dispersion;

[0028] S2, pickling the prepared tubular ceramic support, then rinsing it with pure water and drying it, then spraying a layer of 200nm alumina dispersion on the tubular ceramic support, drying it at 100℃, sintering it at 800℃ for 1h, and repeating it twice, forming a 50nm intermediate layer on the surface of the tubular ceramic support;

[0029] S3, weigh 8g of polyvinyl alcohol and heat it to 90℃ in 400ml of deionized water to dissolve it, to obtain a polyvinyl alcohol aqueous solution, and then dilute the commercial boehmite sol with the polyvinyl alcohol aqueous solution from 20% to 2%, to obtain the required boehmite sol of appropriate concentration;

[0030] S4, spraying a layer of boehmite sol of appropriate concentration evenly on the middle layer of the tubular ceramic support in step S2, drying at 100°C, and sintering at 600°C for 3h to form a nano separation layer on the surface of the middle layer, and obtaining a ceramic support A (γ-Al2O3 ceramic nanofiltration membrane);

[0031] S5. Dissolve 17 ml of tetraisopropyl titanate into 90 ml of ethanol solution to form a mixed solution, immerse the ceramic support A obtained in step S4 into the mixed solution, dissolve 19 ml of acetic acid in 120 ml of ultrapure water, place in a burette, and slowly add dropwise to the mixed solution immersed with the ceramic support A. After the addition is completed, wait for the reaction to occur for 30 minutes, take out the ceramic support A with TiO2 nanoparticles evenly attached, rinse off excess TiO2 nanoparticles with ultrapure water, and dry in an oven to obtain a nanofiltration ceramic membrane with TiO2 evenly distributed on the surface.

[0032] Example 2

[0033] A surface modification method for improving water flux and anti-fouling ability of nanofiltration ceramic membranes, comprising:

[0034] Experimental Materials

[0035] Alumina porous support (tubular membrane / flat membrane, pore size of 200nm, porosity of 41.3%); Alumina (200nm, α-A1203, 99.9%); Methyl cellulose (C20H38011); Anhydrous ethanol (C2H60, ≥99.5%); TiO2 sol; Boehmite sol (20%); Polyvinyl alcohol (PVA, viscosity 30-50mpas); Anhydrous acetic acid (CH3COOH, ≥99.5%); Tetraisopropyl titanate (C12H2804Ti, analytical grade);

[0036] Implementation steps:

[0037] S1. Dissolve 20 g of methyl cellulose in 1000 ml of deionized water at 85°C to obtain a methyl cellulose aqueous solution, then add 120 ml of 15% TiO2 sol to the methyl cellulose aqueous solution to obtain a TiO2 aqueous solution, and finally add 100 g of alumina powder, stir magnetically for 10 min, and then ultrasonicate for half an hour to obtain a 200 nm alumina dispersion;

[0038] S2, pickling the prepared flat ceramic support, then rinsing it with pure water and drying it, then dip-coating a layer of 200nm alumina dispersion on the flat ceramic support, drying it at 100℃, and sintering it at 800℃ for 1h, to form a 50nm intermediate layer on the surface of the flat ceramic support;

[0039] S3, weigh 18g of polyvinyl alcohol and heat it in 1000ml of deionized water at 90℃ to dissolve it to obtain a polyvinyl alcohol aqueous solution, and then dilute the commercial boehmite sol with the polyvinyl alcohol aqueous solution from 20% to 2%. The desired boehmite sol of appropriate concentration can be obtained;

[0040] S4, uniformly dip-coating a layer of boehmite sol of appropriate concentration on the intermediate layer of the flat ceramic support in step S2, drying at 100°C, and sintering at 600°C for 3h to form a nano separation layer on the surface of the intermediate layer, thereby obtaining a ceramic support A (γ-Al2O3 ceramic nanofiltration membrane);

[0041] S5. Dissolve 60 ml of tetraisopropyl titanate into 300 ml of ethanol solution to form a mixed solution, immerse the ceramic support A obtained in step S4 into the mixed solution, dissolve 60 ml of acetic acid in 360 ml of ultrapure water, place in a burette, and slowly add dropwise to the mixed solution immersed with the ceramic support A. After the addition is completed, wait for the reaction to occur for 40 minutes, take out the ceramic support A with TiO2 nanoparticles evenly attached thereto, rinse off excess TiO2 nanoparticles with ultrapure water, and dry in an oven to obtain a nanofiltration ceramic membrane with TiO2 evenly distributed on the surface.

[0042] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A surface modification method for improving water flux and anti-fouling ability of nanofiltration ceramic membrane, characterized in that: The steps include: S1. Dissolve methyl cellulose in deionized water by heating to obtain a methyl cellulose aqueous solution, then add TiO2 sol to the methyl cellulose aqueous solution to obtain a TiO2 aqueous solution, and finally add weighed alumina powder, stir magnetically for 10 minutes and then ultrasonicate for half an hour to obtain a 200 nm alumina dispersion; S2. Spray or dip a layer of 200 nm aluminum oxide dispersion on the ceramic support, dry at 100° C., and sinter at 800° C. for 13 h to form a 50 nm intermediate layer on the surface of the ceramic support; S3, weigh polyvinyl alcohol and heat it in deionized water to dissolve it to obtain a polyvinyl alcohol aqueous solution, and then dilute the commercial boehmite sol with the polyvinyl alcohol aqueous solution from 20% to 2%-8% to obtain the desired boehmite sol of the appropriate concentration; S4, evenly spray or dip-coat a layer of boehmite sol of appropriate concentration on the middle layer of the ceramic support in step S2, dry at 100°C, and sinter at 600°C for 2-4h to form a nano separation layer on the surface of the middle layer, thereby obtaining a ceramic support A; S5. Dissolve tetraisopropyl titanate in ethanol solution to form a mixed solution, immerse the ceramic support A obtained in step S4 into the mixed solution, dissolve acetic acid in ultrapure water, place it in a burette, and slowly add it dropwise to the mixed solution immersed with the ceramic support A. After the addition is completed, wait for a period of time for the reaction, take out the ceramic support A, rinse off excess TiO2 particles with ultrapure water, and dry it in an oven to obtain a nanofiltration ceramic membrane with TiO2 evenly distributed on the surface.

2. A surface modification method for improving water flux and anti-fouling ability of nanofiltration ceramic membrane according to claim 1, characterized in that: The concentration of methylcellulose in the methylcellulose aqueous solution in step S1 is in the range of 1% to 8%.

3. The surface modification method for improving water flux and anti-fouling ability of nanofiltration ceramic membrane according to claim 1, characterized in that: The TiO2 content of the TiO2 aqueous solution in step S1 is in the range of 0.5% to 3%.

4. The surface modification method for improving water flux and anti-fouling ability of nanofiltration ceramic membrane according to claim 1, characterized in that: The aluminum oxide content of the 200 nm aluminum oxide dispersion in step S1 is in the range of 3% to 8%.

5. The surface modification method for improving water flux and anti-fouling ability of nanofiltration ceramic membrane according to claim 1, characterized in that: The polyvinyl alcohol concentration of the polyvinyl alcohol aqueous solution in step S2 is 2%-5%.

6. The surface modification method for improving water flux and anti-fouling ability of nanofiltration ceramic membrane according to claim 1, characterized in that: The volume range of acetic acid in step S5 is 19 ml-60 ml, and the volume range of ultrapure water is 120 ml-360 ml.

7. The surface modification method for improving water flux and anti-fouling ability of nanofiltration ceramic membrane according to claim 1, characterized in that: The time for waiting for the reaction after the dropwise addition in step S5 is 30-40 minutes.

Citation Information

Patent Citations

  • Method for preparing high-flux gas-solid separation ceramic membrane based on phase inversion method

    CN117531381A